ΔR2* gadolinium‐diethylenetriaminepentacetic acid relaxivity in venous blood. Issue 4 (10th May 2012) - Patil, Vishal; Johnson, Glyn
<x xml:space="preserve">Abstract</x> The accuracy of perfusion measurements using dynamic, susceptibility‐weighted, contrast‐enhanced MRI depends on estimating contrast agent concentration in an artery, i.e., the arterial input function. One of the difficulties associated with obtaining an arterial input function are partial volume effects when both blood and brain parenchyma occupy the same pixel. Previous studies have attempted to correct arterial input functions which suffer from partial volume effects using contrast concentration in venous blood. However, the relationship between relaxation and concentration (C) in venous blood has not been determined in vivo. In this note, a previously employed fitting approach is used to determine venous relaxivity in vivo. In vivo relaxivity is compared with venous relaxivity measured in vitro in bulk blood. The results show that the fitting approach produces relaxivity calibration curves which give excellent agreement with arterial measurements. Magn Reson Med 69:1104–1108, 2013. © 2012 Wiley Periodicals, Inc.